Physical Properties and Characterization of Cassava Peel Waste Modified by Esterification - Suci Susanti; Denis Al Karoma; Dian Mulyani; Masruri Masruri (The Journal of Pure and Applied Chemistry Research, 2017)
Cassava starch (Manihot esculenta) is polysaccharide compound which comprises of amylose and amylopectin. This paper demonstrated the characterization result of cassava peel waste modified by esterification with acetic acid and oleic acid. The products were analyzed by FT-IR, PSA, SEM, and XRD. FT-IR results represented carbonyl compound. DS value of acetic acid and oleic acid modification is 0.63 and 0.56, respectively. Characterization by PSA found the distribution frequency was 358.19 mm. SEM analysis was obtained rigid structure. From XRD result, the crystallinity of modified flour better than without modification.